Propuesta de mejora en la gestión de almacenamiento y abastecimiento de materia prima en un almacén dedicado a la producción de productos de bioseguridad - Calderón Menacho, Angélica Rouse (2024)
The pharmaceutical industry has more and more competition; since the beginning of the pandemic many companies in this field closed their doors due to the economic crisis in the country; however, few small companies knew how to move forward, among them is this company dedicated to the production of biosafety products. Until last year, this company led the pharmaceutical field with its products, but other organizations surpassed themselves, started with more accessible prices and faster deliveries of biosafety products, thus generating competition that previously did not exist for the aforementioned laboratory. First, the current situation of the organization's storage and supply management will be presented; for the development of the methodology, the 5 Why's, the ABC Classification, LAYOUT Analysis and the 5 “S” will be applied; the transfer time when dispatching raw materials will be analyzed and the implementation of a new Layout and an improved storage of the products found in it will be proposed in order to maintain storage control. Afterwards, case studies that successfully applied storage and supply management will be presented. Due to the improvement of the company, this research is entitled “Proposal for improvement in the management of storage and supply of raw materials in a warehouse dedicated to the production of biosafety products”; its general objective is to determine how the application of the management of storage and supply of raw materials improves productivity in the warehouse of the laboratory mentioned above, seeking customer satisfaction by receiving a quality product at a good price, which is delivered in the shortest possible time.